1986
DOI: 10.1099/0022-1317-67-1-203
|View full text |Cite
|
Sign up to set email alerts
|

RNA 2 of Red Clover Necrotic Mosaic Virus Determines Lesion Morphology and Systemic Invasion in Cowpea

Abstract: SUMMARYRed clover necrotic mosaic virus (RCNMV) has two RNA species of mol. wt. about 1.5 x 106 (RNA 1) and 0.5 × 106 (RNA 2). An English strain (H) and a Czechoslovakian strain (TpM-34)of RCNMV could be distinguished serologically, by solid-phase RNA hybridization analysis (Northern blotting) and by the symptoms they induced in cowpea. Studies of pseudorecombinants, formed following inoculation of plants with heterologous combinations of the RNA species of each strain, showed that RNA 2 determines the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
2
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
26
2
1
Order By: Relevance
“…It has been demonstrated that physicochemical and serological features of progeny virus are determined by the donor RNA-1 (Pappu & Hiruki, 1989;Okuno et al, 1983). Similar work on red clover necrotic mosaic virus (RCNMV) Osman et al, 1986Osman et al, , 1991aPaje-Manalo & Lommel, 1989), another member of the dianthovirus group, has demonstrated that RNA-2 is responsible for cell-to-cell virus movement and that it plays a role in the development of disease symptoms in infected plants. To gain further understanding of the function of SCNMV RNA-2, we have determined the primary structures of RNA-2s of SCNMV-38 and -59.…”
mentioning
confidence: 73%
“…It has been demonstrated that physicochemical and serological features of progeny virus are determined by the donor RNA-1 (Pappu & Hiruki, 1989;Okuno et al, 1983). Similar work on red clover necrotic mosaic virus (RCNMV) Osman et al, 1986Osman et al, , 1991aPaje-Manalo & Lommel, 1989), another member of the dianthovirus group, has demonstrated that RNA-2 is responsible for cell-to-cell virus movement and that it plays a role in the development of disease symptoms in infected plants. To gain further understanding of the function of SCNMV RNA-2, we have determined the primary structures of RNA-2s of SCNMV-38 and -59.…”
mentioning
confidence: 73%
“…When RNAs of RCNMV-TpM-34 and RCNMV-Aus were separated (Osman et al, 1986;Osman & Buck, 1987) and inoculated in homologous or heterologous mixtures to cowpea leaves, lesions were formed in numbers similar to those induced by inocula of the parent isolates. Hence these two isolates can form pseudorecombinants in both directions.…”
mentioning
confidence: 99%
“…Hence these two isolates can form pseudorecombinants in both directions. Previous studies have shown that isolates of RCNMV and other dianthoviruses can form pseudorecombinants either bilaterally (Okuno et al, 1983;Osman et al, 1986) or unilaterally (Rao & Hiruki, 1987). The ability to form viable pseudorecombinants probably depends, amongst other things, on the ability of the viral RNA replicase to recognize sequences at the 5' and 3' ends of the heterologous RNA.…”
mentioning
confidence: 99%
See 2 more Smart Citations